Applying Fuzzy set method for solving mechanical engineering problems (Determining residual service life) - Al-waely, Waail Mahmod; Khalil, Maad M. (Iraqi Journal for Electrical and Electronic Engineering, 2010)
In this paper we use fuzzy set method to solve one of the important problems in mechanical engineering (the residual service life). The residual service life for rolling stock can change depending on it’s using conditions. The Paper offer’s a new method depending on fuzzy set method by using the material mechanical and chemical corrosion mathematical model.